Targeting Multiple Binding Sites on Cholera Toxin B with Glycomimetic Polymers Promotes Formation of Protein–Polymer Aggregates - Youn, Gyusaang (Biomacromolecules, 2020)
The canonical binding site on the B subunit of cholera toxin (CTB) binds to GM1 gangliosides on host cells. However, the recently discovered noncanonical binding site on CTB with affinity for fucosylated molecules has raised the possibility that both sites can be involved in initiating intoxication. Previously, we showed that blocking CTB binding to human and murine small intestine epithelial cells can be increased by simultaneously targeting both binding sites with multivalent norbornene-based glycopolymers [ACS Infect. Dis. 2020, 6, 5, 1192–1203]. However, the mechanistic origin of the increased blocking efficacy was unclear. Herein, we observed that mixing CTB pentamers and glycopolymers that display fucose and galactose sugars results in the formation of large aggregates, which further inhibits binding of CTB to human granulocytes. Dynamic light scattering analysis, small-angle X-ray scattering analysis, transmission electron microscopy, and turbidimetric assays revealed that the facial directionality of CTB promotes interchain cross-linking, which in turn leads to self-assembly of protein–polymer networks. This cross-linking-induced self-assembly occurs only when the glycopolymer system contains both galactose and fucose. In an assay of the glycopolymer’s ability to block CTB binding to human granulocytes, we observed a direct correlation between IC(50) and self-assembly size. The aggregation mechanism of inhibition proposed herein has potential utility for the development of low-cost macromolecular clinical therapeutics for cholera that do not have exotic architectures and do not require complex synthetic sequences.